Microplastics as a Vector for Exposure to Hydrophobic Organic Chemicals in Fish: A Comparison of Two Polymers and Silica Particles Spiked With Three Model Compounds - Ašmonaitė, Giedrė; Tivefälth, Malin; Westberg, Emelie; Magnér, Jörgen; Backhaus, Thomas; Carney Almroth, Bethanie (Frontiers in Environmental Science, 2020)
The role of microplastics as chemical vectors delivering environmental contaminants into biota has been proposed, but their environmental relevance remains an issue of a debate. In this paper we compared the propensity and relative importance of synthetic polymer microparticles (glassy polystyrene (PS) and rubbery polyethylene (PE)) and silica glass particles (SG) to act as vectors for hydrophobic organic chemicals (HOCs) into fish after ingestion. Particles were spiked with three HOCs (17α-ethinylestradiol, chlorpyrifos and benzo(α)pyrene), which differ in hydrophobicity and induce well-known biomarker responses. Three-spined stickleback were exposed to 8 different diets: control diets (1), diets with non-spiked particles (2-4), diets containing a mixture of particles spiked with 3 model contaminants (5-7) and, finally, diets loaded with only the chemical mixture (8), for 14 days. Chemical sorption onto the particles was quantified and chemical transfer into the fish was investigated via biomarkers (CYP1a, ERα, VTG and AChE) in fish intestine, liver and brain and quantification of HOCs in fish muscle. Results demonstrated particle-mediated chemical transfer of moderately hydrophobic contaminants into fish. While PS and PE particles mediated higher chemical transfer and tissue accumulation of 17α-ethinylestradiol and chlorpyrifos than SG, the overall chemical transfer was found to be very low. The present work suggested that chemical sorption, desorption and subsequent transfer of chemicals in vivo depends on multiple interconnected factors, including physicochemical properties of particles and contaminants, as well as toxicokinetic and toxicodynamic interactions. The biomarker approach was, however, suboptimal for assessing chemical transfer when addressing particle-associated chemical mixtures.